Description of Outbreak of Acute Intestinal Infections in the Republic of Dagestan - Z. G. Tagirova; D. R. Akhmedov; M. M. Magomedov; M. A. Gasanova; Z. M. Daniyalbekova (Эпидемиология и вакцинопрофилактика)
The incidence of acute intestinal infections (AII) in the Republic of Dagestan in 2015 was higher than in the Russian Federation as whole, 4.6 times. In the structure of the AII of the revealed etiology, Shigellosis plays a predominant role. The article analyzes the outbreak of shigellosis, registered in 2016 in Makhachkala